Ecological assessment of Iris hookeriana across subalpine and alpine regions of the Hindu-Himalayas - Khan, Muhammad Shakeel; Khan, Shujaul Mulk; Abdullah,; Liu, Jie; Wu, Zeng-Yuan; Hussain, Jawad; Zeb, Shakil Ahmad; Mohammad, Nazir; Batool, Zareena; Saqib, Zafeer; Afza, Rabia; Manan, Fazal; et al. (Frontiers in Forests and Global Change, 2025)
IntroductionThe Hindu-Himalayan region, a global biodiversity, hotspot harbors numerus endemic plant species that contribute significantly to ecosystem stability. Among these, Iris hookeriana, an endemic perennial herb, thrives in the subalpine and alpine zones of the Hindu-Himalayas. The study aimed to assess the population dynamics of Iris hookeriana, assesses the primary threats to its survival, and explores its ecological associations along with with indicator species.MethodsFieldwork was conducted across 35 distinct sites, at the elevation range of 2,500 m–3,900 m above sea level. A random stratified sampling method using quadrats, was employed to assess both qualitative and quantitative plant characteristics. Edaphic, topographic, geographic coordinates, and elevation Global Positioning System (GPS) data were recorded on each sampling site. Plant species associations were analyzed using 5 m2 × 5 m2 quadrat for shrubs and 1 m2 × 1 m2 quadrat for herbaceous vegetation. The relationships between species composition and environmental variables were analyzed via Statistical analyses, including Detrended Correspondence Analysis (DCA), Canonical Correspondence Analysis (CCA), Two-Way Cluster Analysis (TWCA), and Indicator Species Analysis (ISA), were conducted using PCORD version 5.0.ResultsSeventy associated plant species from 26 families were identified across 35 sampling sites, revealing four major plant associations: (1) Arenaria-Viola association, (2) Nepeta-Oxytropis association, (3) Phlomis-Prunella association, and (4) Bistorta-Carex association. These associations exhibited significant correlations (p < 0.05). The identification of these four novel plant associations provides a crucial baseline for understanding the ecological dynamics of the subalpine and alpine ecosystems. The study emphasizes the significant role of environmental factors i.e., altitude, organic matter, pH, humidity, total dissolved solid, electrical conductivity, nitrogen, phosphorus, silt, and clay content in shaping the Iris hookeriana population within the subalpine and alpine zone of Hindu-Himalayan Mountains.DiscussionThe findings show that indicator species and plant associations vary with changing environmental conditions, providing valuable insights for sustainable biodiversity management in subalpine and alpine ecosystems of the Hindu-Himalayan mountains.